Снижение антистрессовыми препаратами нервнопаралитического действия высокой концентрации аммония на рыб - Потрохов, А.С. (Видавничий дім "Академперіодика" НАН України, 2008)
A possibility of weakening the development of fishes reactions by the type of chemical stress on the action of ammonium nitrogen by means of application of different tranquilizers is investigated. It is shown that, in the first hours of the influence of toxin, the neuroparalytic effects at fishes are taken off, and their death is considerably slowed due to fenazepam and sodium barbytal.